2016
DOI: 10.1021/acs.langmuir.5b04211
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Aggregate Transitions in Mixtures of Cationic Ammonium Gemini Surfactant with Anionic Glutamic Acid Surfactant in Aqueous Solution

Abstract: The aggregation behaviors of the mixtures of cationic gemini surfactant 1,4-bis(dodecyl-N,N-dimethylammonium bromide)-2,3-butanediol (C12C4(OH)2C12Br2) and anionic amino acid surfactant N-dodecanoylglutamic acid (C12Glu) in aqueous solution of pH = 10.0 have been studied. The mixture forms spherical micelles, vesicles, and wormlike micelles at 25 °C by changing mixing ratios and/or total surfactant concentration. Then these aggregates undergo a series of transitions upon increasing the temperature. Smaller sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Due to their enhanced properties, catanionic mixtures containing various dimeric surfactants have been subject of numerous papers [25,[35][36][37][38][39][40][41][42][43][44][45][46]. The most investigated are catanionic mixtures containing bis-quaternary ammonium salts with the alkyl spacers.…”
Section: Catanionic Mixtures Of Oligomeric and Monomeric Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their enhanced properties, catanionic mixtures containing various dimeric surfactants have been subject of numerous papers [25,[35][36][37][38][39][40][41][42][43][44][45][46]. The most investigated are catanionic mixtures containing bis-quaternary ammonium salts with the alkyl spacers.…”
Section: Catanionic Mixtures Of Oligomeric and Monomeric Surfactantsmentioning
confidence: 99%
“…Aggregation behavior in mixtures of cationic dimeric surfactants derived from dodecyltrimethylammonium chloride (C 12 TACl, Figure 4) and SDS by means of small-angle neutron scattering (SANS) and small-angle X-ray scattering (SAXS) was investigated by Prévost et al Figure 6), and anionic amino acid surfactant, N-dodecanoylglutamic acid (C 12 Glu, Figure 5) at pH = 10.0 [42]. At 25 °C small spherical micelles, vesicles and entangled worm-like micelles were detected in the system.…”
Section: Catanionic Mixtures Of Oligomeric and Monomeric Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Switchable wormlike micelles are one type of stimuli-responsive fluid whose reversible regulation of the rheological behaviors can be realized through introducing an external stimulus [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Based on the influence of the stimulus on these weak interactions, a series of stimuli-responsive wormlike micelles have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al 15,17 rst reported a temperature-induced micelleto-vesicle transition (MVT) in a cationic (dodecyltriethylammonium bromide)/anionic (sodium dodecyl sulfate) surfactant system, and it was observed that the transition from cylindrical micelles to vesicles was accompanied by an increase in turbidity of the solution with increasing temperature. Wang et al 22 reported effects of temperature on the transition of aggregates in a mixed system of ammonium gemini surfactant C 12 C 4 (OH) 2 C 12 Br 2 with anionic amino acid monomeric surfactant C 12 Glu. A series of transition of surfactant aggregates was observed upon increasing the temperature, e.g.…”
Section: Introductionmentioning
confidence: 99%